PENGARUH MODEL PEMBELAJARAN Two Stay Two Stray TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PKn DI KELAS V SD NEGERI 094155 RAMBUNG MERAH - Dita Cahaya Simbolon; Emelda Thesalonika; Yanti Arasi Sidabutar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine how big the influence of the Two Stay Two Stray Learning Model is on the Learning Outcomes of Class V Students Theme 2 Sub-theme 1 Clean Air for Health on Civics learning at SDN 0941155 Rambulng Melrah. There are 2 hypotheses in this research, namely: (Ha) There is an influence of the Two Stay Two Stray model on student learning outcomes in Civics subjects in class V of SD Negeri 094155 Rambung Merah FY 2023/2024. (Ho) There is no influence of the Two Stay Two Stray model on student learning outcomes in Civics subjects in class V of SD Negeri 094155 Rambung Merah T.A 2023/2024. This research was carried out in the 2023/2024 academic year in October. This research method is an experiment with a pre-experimental design research type with a One-Group Pretest-Posttest Design research design. The sample for this research was 30 students consisting of 11 male students and 19 female students. The data collection techniques used are tests and documentation. The data was processed using the N-Gain test statistical analysis technique. Based on the normality test results obtained, the learning outcomes of class V students were normally distributed with the final value of the N-Gain test having a significance of 0.57 > 0.05. From these results, it can be seen that Ha was accepted, which means that there is an influence of using the Two Stay Two Stray learning model on student learning outcomes in Civics subjects in Class V of SD Negeri 094155 Rambung Merah FY 2023/2024..